Roflumilast promotes memory recovery and attenuates white matter injury in aged rats subjected to chronic cerebral hypoperfusion. (August 2018) - Santiago, Amanda; Soares, Lígia Mendes; Schepers, Melissa; Milani, Humberto; Vanmierlo, Tim; Prickaerts, Jos; Weffort de Oliveira, Rúbia M.
Abstract: Chronic cerebral hypoperfusion (CCH) has been associated with aging-related vascular dementia, including Alzheimer's disease. It can be induced by the four-vessel occlusion/internal carotid artery (4VO/ICA) model in aged rats, resulting in persistent memory deficits, white matter injury, and significant neuronal loss in the hippocampus and cerebral cortex. The phosphodiesterase type 4 inhibitor (PDE4-I) roflumilast has been reported to have pro-cognitive effects in several behavioral paradigms. The present study evaluated the effects of repeated roflumilast treatment in aged rats that were subjected to CCH. After surgery, roflumilast (0.003 and 0.01 mg/kg) was administered intraperitoneally once per day for 29 days. Memory performance was assessed in the aversive radial maze (AvRM) 7, 14, and 21 days after CCH. The effects of roflumilast on hippocampal neurodegeneration and white matter injury were investigated using Nissl and Kluver-Barrera staining, respectively. Western blot and RT-qPCR were used to explore microglial polarization using M1 (Iba-1 and iNOS) and M2 (Arginase-1) markers. Chronic cerebral hypoperfusion caused persistent memory deficits, hippocampal neurodegeneration, and vacuolization and fiber disarrangement in white matter. Repeated roflumilast treatment restored CCH-induced cognitive impairments in aged rats but in the absence of the rescue of hippocampal neurons. Attenuation of white matter injury was detected in the optic tract in aged CCH rats that were treated with roflumilast. In vitro, roflumilast increased Arg-1 gene expression in myelin-laden primary microglia. The present data suggest that roflumilast might be useful for the treatment of cognitive sequelae associated with CCH. Highlights: Roflumilast restored cognitive impairments in aged rats with chronic cerebral hypoperfusion (CCH). Roflumilast attenuated white matter injury in aged rats with CCH. Roflumilast changed inflammatory signaling in the central nervous system resident cells. Roflumilast ncreased Arg-1 gene expression in myelin-laden primary microglia.